How Can International Students be Supported in Post-Secondary Education in Canada? A Qualitative Study - Sasse, Claudia (Journal of University Teaching and Learning Practice, 2025)
International students may encounter culture shock, a state of confusion or disorientation that arises as they adapt to an unfamiliar culture and leave behind their familiar one (Amos & Lordly, 2014). Since international students in Canada come from diverse countries, their perceptions of post-secondary education can vary greatly, often leading to academic challenges. This qualitative study, drawing on Acculturation Theory, explores how post-secondary institutions can more effectively address international students' needs. Data was collected through four focus group interviews with faculty, staff, and international students at a Western Canadian post-secondary institution. Students shared personal and academic needs while faculty and staff discussed their awareness of these needs and resource utilization. Findings emphasized the importance of promoting intercultural competence and personalizing learning experiences. Faculty and staff expressed a need for additional training and resources. The key implication is that effective support requires institutions to understand students' home-country educational perspectives and provide appropriate campus resources.